The Use of Oral Antibiotics to Prevent Surgical Site Infection on Postoperative Modified Radical Mastectomy Patients in Dr. Soetomo General Hospital, Surabaya - Hadi, Norman; Ishardyanto, Hantoro (Folia Medica Indonesiana, 2020)
Surgical operations on modified radical mastectomy are considered clean procedures by the Centers for Disease Control and Prevention (CDC) wound classification system. Despite this, higher than expected Surgical Site Infection (SSI) rates are reported, varying from 1 % to 26 % across the literature. Some surgeons also prescribe postoperative prophylaxis for postoperative modified radical mastectomy patients to prevent infection despite its lack of proven efficacy. The aim of this study is to analyze the use of oral antibiotics to prevent Surgical Site Infection (SSI) on postoperative modified radical mastectomy patients in Dr. Soetomo General Hospital. This study was double-blinded randomized control trial of 60 postoperative modified radical mastectomy patients (2 groups) during the period of December 2017 to March 2018. Samples were prospectively divided into two groups (random sampling), in group A (n=30) patients received single dose prophylactic antibiotics and continued with oral antibiotics postoperative (Cefadroxil 2 x 500 mg) during 7 days and in group B (n=30) patients received single dose prophylactic antibiotics and continued without postoperative antibiotics (placebo). Both groups were evaluated clinically for surgical site infection up to 30 days. There was no statistically significant difference in both groups p=1 (p>0.05). There was no incidence of surgical site infection in both groups during the 30-day follow-up period (days 3, 7, 14 and 30). There was no difference in the surgical site infection rate among those who received oral postoperative antibiotics prophylactic and without antibiotics (placebo) on postoperative modified radical mastectomy patients in Dr. Soetomo General Hospital. Because of the potential adverse events associated with antibiotic use, further evaluation of this practice is required.